ChemInform Abstract: 2‐Aminobenzothiazole Derivatives: Search for New Antifungal Agents. Issue 43 (7th October 2013) - Catalano, Alessia; Carocci, Alessia; Defrenza, Ivana; Muraglia, Marilena; Carrieri, Antonio; Van Bambeke, Francoise; Rosato, Antonio; Corbo, Filomena; Franchini, Carlo
Abstract Derivatives (IIe, f) show the highest activity against Candida albicans, Candida parapsilosis and Candida tropicalis along with no cytotoxic effect on human THP‐1 cells.